Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Changes in Soil Phosphorus Fractions Across Soil Depths Under Continuous Wheat-Faba Bean Intercropping - Wenlian Bai; Rong Dai; Ling Qian; Weiwu Changjin; Li Tang; Yi Zheng; Jingxiu Xiao (Journal of Soil Science and Plant Nutrition, 2026)

Distribution and potential drivers of methane emissions from deep-sea environments in Haima cold seep areas - Li Tang; Jing-Chun Feng; Can-Rong Li; Xiao Chen; Hui Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Introduction Tracing methane originating from deep-sea environments is essential for understanding the global methane budget. However, knowledge regarding the mechanisms governing methane transfer from deep-sea sediments to the water column in cold seep environments remains limited. This study aims to quantitatively investigate the distribution of methane and identify its controlling factors within the Haima cold seep areas. Methods A comprehensive analysis was conducted to investigate the distribution characteristics of methane and its potential drivers in both the water column and sediment porewaters within the Haima cold seep areas. Results The key findings are: (1) Haima cold seeps serve as a methane source to the atmosphere, with pronounced spatial heterogeneity in emission strength across the monitored regions. (2) The vertical distribution of methane is influenced by multiple environmental factors. Key factors in sediment porewaters include sediment depth, porosity, inorganic carbon (IC), chloride (Cl – ), and sulfate (SO 4 2– ), whereas silicate (SiO 3 2– ) and dissolved oxygen (DO) are primary regulators in the water column. (3) Sediments represent a significant methane source for bottom seawater, with methane consumption being more pronounced in seepage areas than in non-seepage areas. Discussion This study demonstrates that methane dynamics in the Haima cold seep are complex and driven by a combination of physical, chemical, and biological processes across the sediment–water interface. The identified key drivers underscore the importance of porewater geochemistry and water column biogeochemistry in controlling methane release. These findings significantly advance our understanding of methane transport in deep-sea seep systems and provide crucial insights for refining global methane flux estimates.

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Effects of soil labile carbon fractions and microbes on GHG emissions from flooding to drying in paddy fields - Yi Xiao; Rong Huang; Zongjin Zhang; Vanessa N.L. Wong; Xingyu Li; Xiaoyan Tang; Youlin Luo; Yingjie Wu; Jiang Liu; Shiwei Li; Changquan Wang; Bing Li (Journal of Environmental Sciences, 2025)

Interploidy hybridization enhances floral phenotypic diversity of Iris × norrisii tetraploids via 2n pollon - Jiacheng Tang; Liya Ding; Yike Gao; Rong Liu; Jianhua Xiao; Yi Lv; Ziyi Wang; Qixiang Zhang (Euphytica, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

The diverse sleep structure of mid-day nap in college students - Qin Xiao; Xueqi Sun; Guoxin Zeng; Xin Luo; Qian Jiang; Rong Ren; Xiangdong Tang; Chao He; Zhian Hu; Fenlan Luo; Jie Yan (Sleep and Biological Rhythms, 2025)

Machine learning for time series prediction of valley deformation induced by impoundment for high arch dams - Hang-Hang Zang; Dian-Qing Li; Xiao-Song Tang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2025)

1DCNN-based prediction methods for subsequent settlement of subgrade with limited monitoring data - Sen-Lin Xie; Anfeng Hu; Meihui Wang; Zhi-Rong Xiao; Tang Li; Chi Wang (European Journal of Environmental and Civil Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Protecting anthocyanins of postharvest blueberries through konjac glucomannan/low-acyl gellan gum coatings contained thymol microcapsule during low-temperature storage - Jing Xie; Dur E. Sameen; Zhenkun Xiao; Huiyan Zhu; Yunya Lai; Tingting Tang; Xingyu Rong; Fengmei Fu; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Efficient Bayesian updating for deformation prediction of high rock slopes induced by excavation with monitoring data - Dian-Qing Li; Hang-Hang Zang; Xiao-Song Tang; Guan Rong (Engineering Geology, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Catalytically ultrathin titania coating to enhance energy storage and release of aluminum hydride via atomic layer deposition - Zhijia Hu; Xingxing Xu; Huachen Shao; Ruidong Luo; Mingxuan Wang; Gen Tang; Xiao Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

Three-way junction-mediated three-letter coded SDA cascade CRISPR/Cas12a system for circRNA detection - Di Wu; Xin Liu; Lujia Tang; Baiying Li; Rong Zhao; Tong Feng; Xiangyang Xiao; Guoming Xie; Wenli Feng (Chemical Engineering Journal, 2024)

Silica's silent threat: Contributing to skin fibrosis in systemic sclerosis by targeting the HDAC4/Smad2/3 pathway - Bingsi Tang; Yaqian Shi; Zhuotong Zeng; Xinglan He; Jiangfan Yu; Ke Chai; Jiani Liu; Licong Liu; Yi Zhan; Xiangning Qiu; Rui Tang; Yangfan Xiao; et al. (Environmental Pollution, 2024)

PANI/GO and Sm co-modified Ti/PbO2 dimensionally stable anode for highly efficient amoxicillin degradation: Performance assessment, impact parameters and degradation mechanism - Zeyi Wang; Luyao Zhang; Rong Su; Lu Yang; Feng Xiao; Lichuan Chen; Ping He; Dingming Yang; Yali Zeng; Yun Zhou; Ying Wan; Bin Tang (Journal of Environmental Management, 2024)

Remote-Sensing Estimation of Upwelling-Frequent Areas in the Adjacent Waters of Zhoushan (China) - Teng Xiao; Jiajun Feng; Zhongfeng Qiu; Rong Tang; Aibo Zhao; Kapo Wong; Jin Yeu Tsou; Yuanzhi Zhang (Journal of Marine Science and Engineering, 2024)
Upwelling, which mixes deep and surface waters, significantly enhances the productivity of surface waters and plays a critical role in marine ecosystems, especially in key fishing areas like Zhoushan. This study utilized merged sea surface temperature data and an upwelling edge detection algorithm based on temperature gradients to analyze the characteristics of upwelling in Zhoushan and the Yangtze River Estuary over the past 28 years. The results indicate that upwelling in Zhoushan begins in April, peaks in July, gradually weakens, and disappears by October. The phenomenon is most pronounced during the summer months (June to August), with significant spatial distribution differences in April and September. Notably, high probability values of upwelling centers and core areas are mainly concentrated near Ma’an Island, Zhongjieshan Island, and Taohua Island. In these areas, upwelling remains stable during the summer, forming a unique “footprint” distribution pattern, and these are also the locations of the Zhoushan National Marine Ranch. From April to August, the extent of the upwelling area gradually decreases and stabilizes. These findings emphasize the frequent upwelling activity around Zhoushan and its significant contribution to the formation of local fisheries. Additionally, considering that the formation of natural upwelling in the East China Sea depends on the southern monsoon, the study suggests establishing artificial upwelling systems during periods unfavorable for natural upwelling, based on high probability areas, to enhance fishery yields and support the development of local fisheries.

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Multimedia distribution, partitioning, sources, comprehensive toxicity risk and co-occurrence network characteristics of trace elements in a typical Chinese shallow lake with high antibiotic risk - Ling Zhang; Junhong Bai; Yujia Zhai; Kegang Zhang; Yaqi Wang; Ruoxuan Tang; Rong Xiao; Milko A. Jorquera (Journal of Hazardous Materials, 2024)

Pollution levels and potential ecological risks of trace elements in relation to bacterial community in surface water of shallow lakes in northern China before and after ecological water replenishment - Ling Zhang; Junhong Bai; Yujia Zhai; Kegang Zhang; Yaqi Wang; Ruoxuan Tang; Rong Xiao; Milko A. Jorquera (Journal of Contaminant Hydrology, 2024)

Composition of DOM along the depth gradients in the paddy field treated with crop straw for 10 years - Rong Huang; Zheng Li; Yi Xiao; Jiang Liu; Tao Jiang; Ouping Deng; Xiaoyang Tang; Yingjie Wu; Qi Tao; Qiquan Li; Youlin Luo; Xuesong Gao; et al. (Journal of Environmental Management, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

RETRACTED ARTICLE: Liquiritin reduces ferroptosis in doxorubicin-induced cardiotoxicity through targeting SLC7A11/GPX4 pathway - Mei Wang; Meng Liu; Lijing Tang; Lixian Shen; Junhui Xiao; Rong Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

B4C/Ce co-modified Ti/PbO2 dimensionally stable anode: Facile one-step electrodeposition preparation and highly efficient electrocatalytic degradation of tetracycline - Zeyi Wang; Rong Su; Maojie Zhao; Luyao Zhang; Lu Yang; Feng Xiao; Weishan Tang; Lichuan Chen; Ping He; Dingming Yang (Chemosphere, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Nanoscale evidence of zircon-coffinite-xenotime solid solution observed by atom probe tomography - Wenhao Zhao; Bi-Wen Wang; Li-Xin Gu; Xu Tang; Yu Liu; Muhammad Awais; Xiao-Chi Liu; Xian-Hua Li; Rong Hu; Qiu-Li Li (Chemical Geology, 2023)

Pyroptosis: the potential eye of the storm in adult-onset Still’s disease - Xinglan He; Ruixuan You; Yaqian Shi; Zhuotong Zeng; Bingsi Tang; Jiangfan Yu; Yangfan Xiao; Rong Xiao (Inflammopharmacology, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Effects of organic carbon/elemental carbon and particle size on inhalation bioaccessibility of particle-bound PAHs - Chun-Xue Tang; Ying Dong; Xiao-Yu Yuan; Rong Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2023)

Prediction of daily PM2.5 and ozone based on high-density weather stations in China: Nonlinear effects of meteorology, human and ecosystem health risks - Lili Wang; Boya Liu; Rong Li; Xingfeng Chen; Lili Liu; Xiao Tang; Jingda Liu; Zhiheng Liao; Jinyuan Xin; Yuesi Wang; Bo Hu (Atmospheric Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Environmental polycyclic aromatic hydrocarbon exposure is associated with low back pain - Jiang Chen; Yangjie Liao; Mingjiang Luo; Siliang Tang; Jinshan Huang; Rong Chen; Zhihong Xiao (Environmental Geochemistry and Health, 2023)

Triterpene constituents from the fruits of Cyclocarya paliurus and their anti-HIV-1 IIIB activity - Wen-Chao Tu; Rong-Hua Luo; En Yuan; Kaunda-Joseph Sakah; Quan-Yu Yang; Wei-Lie Xiao; Yong-Tang Zheng; Mei-Feng Liu (Natural Product Research, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

Debris flow characteristics of the compound channels with vegetated floodplains - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Jin-bo Tang; Ke Jin (Science of The Total Environment, 2023)

Lithologic control of soil C:N:P stoichiometry across a climatic gradient in southwest China - Mingming Sun; Rong Yang; Yixin Tang; Dan Xiao; Wei Zhang; Zhihong Xu; Zhihua Shi; Peilei Hu; Hanqing Wu; Kelin Wang (Journal of Soils and Sediments, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Selective recovery of rare earth elements and value-added chemicals from the Dicranopteris linearis bio-ore produced by agromining using green fractionation - Candie Xie; Ye Xiao; Chao He; Wen-Shen Liu; Ye-Tao Tang; Shizhong Wang; Antony van der Ent; Jean Louis Morel; Marie-Odile Simonnot; Rong-Liang Qiu (Journal of Hazardous Materials, 2023)

Directional introduction of pyridine nitrogen functional groups in activated carbon catalysts for the catalytic production of hydrogen: An experimental and DFT calculation - Sida Rong; Liqiang Zhang; Ziyi Yue; Zhanlong Song; Wenjing Tang; Xiao Zhu; Tao Wang; Xiaohan Zhou; Shanjie Cheng; Xiao Xia (Chemical Engineering Journal, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Emerging electrocatalytic activities in transition metal selenides: synthesis, electronic modulation, and structure-performance correlations - Yuting Deng; Sutong Xiao; Yijuan Zheng; Xiao Rong; Mingru Bai; Yuanjiao Tang; Tian Ma; Chong Cheng; Changsheng Zhao (Chemical Engineering Journal, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Molecular Characterization and Dietary Regulation of Glutaminase 1 (gls1) in Triploid Crucian Carp (Carassius auratus) - Yangbo Xiao; Rong Huang; Shenping Cao; Dafang Zhao; Zhuangwen Mao; Chuchu Xiao; Zhehua Xu; Xiaomei Zhou; Xinran Zhang; Yu Zhang; Jianzhou Tang; Junyan Jin; et al. (Fishes, 2022)
Kidney-type glutaminase, encoded by the gls1 gene, plays a critical role in glutamate production and improvement of meat flavor. In this study, a gls1 gene encoding 595 amino acids was cloned from triploid crucian carp (Carassius auratus) (TCC) and showed a high similarity with the gls1 gene found in Cyprinus carpio, Sinocyclocheilus rhinocerous and Puntigrus tetrazona. Comparing the abundance of gls1 in different tissues, we found its expression level in the brain and liver were significantly higher than that in heart, gut, kidney, spleen and muscle. gls1 expression in the brain reached the highest value. In addition, the expression levels of gls1 also appeared different in diurnal variation, with the highest expression seen at 9:00, while it was low at 3:00, 6:00, 15:00 and 24:00. Furthermore, dietary regulation of gls1 expression was investigated in our study. In each feeding trial, each diet was randomly assigned to triplicate tanks. Fish were fed one of the tested diets up to satiation twice daily. The results showed that gls1 expression increased in 32% protein group and decreased in 35–41% protein group. The results of different protein source experiments showed that the expression of gls1 gene in the mixed protein group (the control group) was significantly higher than that in the fish meal and soybean meal groups. Glutamate treatment revealed that appropriate concentrations (0.10 mg/mL in vivo and 2.00% in vitro) of glutamate remarkably improved the expression of gls1. Besides, diets supplemented with 0.80–1.60% lysine-glutamate dipeptide exhibited a down regulatory impact on gls1 expression. In conclusion, this study demonstrated that the expression of gls1 in TCC was increased by 32% protein diet, mixed protein source diet and diet with 2.00% glutamate concentration, while decreased by 0.80–1.60% lysine-glutamate dipeptide. The findings of this study provide a reference for the regulation of gls1 and have a potential application in the optimization of dietary formula in aquaculture.

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Antimicrobial Resistance and Genotype Characteristics of Vibrio scophthalmi Isolated from Diseased Mariculture Fish Intestines With Typical Inter-Annual Variability - Yongxiang Yu; Xiao Liu; Yingeng Wang; Meijie Liao; Miaomiao Tang; Xiaojun Rong; Chunyuan Wang; Bin Li; Zheng Zhang (Frontiers in Marine Science, 2022)
As an intestinal organism settled long-term within the gut of marine fish, Vibrio scophthalmi is a potential object for the bacterium genetic variation and adaptation research. The genetic diversity, antimicrobial resistance phenotype, and genotype of 33 V. scophthalmi isolated from diseased marine fish intestines between 2002 and 2020 were evaluated. The results showed that all isolates were frequently resistant to penicillins, cephalosporins, aminoglycosides, and macrolides and displayed multidrug-resistant (MDR) phenotype in vitro . Thirty percent of isolates were resistant to more than 20 different drugs. The average insensitive (resistant and intermediate) rate of V. scophthalmi isolates was 49.5%~81.8% between 2002 and 2020, but the t-test revealed that there was no significant difference in the drug-resistance rate of V. scophthalmi isolates with typical interannual variability. Eleven antimicrobial resistance genes ( strB , strA , ant(3 ˝)-I , mphA , blaPSE , qnrS , tetC , tetE , tetM , tetS , and int1 ) were detected in these isolates, but the antimicrobial resistance phenotypes and genotypes of these isolates were not consistent. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) analysis indicated that 33 isolates could be divided into two clusters (G1 and G3) and two single isolates (G2 and G4), and the G2 cluster was isolated from South Sea C. undulates with typical geographical species differences. There was no significant correlation between the drug susceptibility and the genetic types of V. scophthalmi isolates. The results reveal the mismatch phenomenon between antimicrobial resistance and genotype of inherent V. scophthalmi in the marine fish intestines, and the antimicrobial susceptibility isolates might be a potential risk source for storage and transmission of resistance genes.

Comparison of nominal and standardized catch per unit effort data in quantifying habitat suitability of skipjack tuna in the equatorial Pacific Ocean - Cheng Zhou; Yuanyuan Hu; Jie Cao; Liuxiong Xu; Xuefang Wang; Rong Wan; Yu Xiao; Jiangfeng Zhu; Hao Tang (Acta Oceanologica Sinica, 2022)

Design, synthesis, and antifungal activity evaluation of novel 2-cyano-5-oxopentanoic acid derivatives as potential succinate dehydrogenase inhibitors - Xue-song Wang; Xiao-rong Tang; Mi-jun Peng; Yong-zhan Mai (Medicinal Chemistry Research, 2022)

Genome-based reclassification of Evansella polygoni as a later heterotypic synonym of Evansella clarkii and transfer of Bacillus shivajii and Bacillus tamaricis to the genus Evansella as Evansella shivajii comb. nov. and Evansella tamaricis comb. nov - Manik Prabhu Narsing Rao; Min Xiao; Dingqi Liu; Rong Tang; Guo-Hong Liu; Wen-Jun Li (Archives of Microbiology, 2022)

Response of Terrigenous Sediment Input to Sea Level Change and East Asian Monsoon Evolution Since 30kyr in the Southwestern Taiwan Basin - Li Feng; Xiuli Feng; Rong Tang; Xiao Xiao; Jie Liu (Journal of Ocean University of China, 2021)

Molecular Characterization of Hsp47 in Grass Carp (Ctenopharyngodon idella) and Its Correlation with Type I Collagen in Response to Fish Aerobic Exercise - Xiao Liang; Ying Wan; Zhiyuan Shen; Yanmei Liu; Dapeng Li; Li Li; Rong Tang; Xi Zhang (Fishes, 2021)
Heat shock protein 47 (Hsp47) is a collagen-specific molecular chaperone that is indispensable for molecular maturation of collagen. In this study, hsp47 and hsp47-like cDNAs were cloned and characterized in grass carp (Ctenopharyngodon idella). The cDNAs were 1212 and 1218 base pairs long, respectively, and included an open reading frame encoding 403 and 405 amino acids. The molecular phylogeny based on the deduced amino acid sequences indicated that the correct sequences of the hsp47 and hsp47-like cDNA were obtained and the deduced proteins clustered distinctly into teleost clades. Primary structure analysis and characterization of Hsp47 and Hsp47-like shared the basic structure and biofunctions of Hsp47 in vertebrates. The spatial pattern of gene expression revealed that hsp47 and hsp47-like were relatively ubiquitous in different tissues and highly expressed in heart and skin. The expression levels of hsp47 and hsp47-like and type I collagen mRNAs varied similarly in different tissues. Type I collagen content increased significantly with the increase of water velocity in the muscle of grass carp in response to aerobic exercise. Among the gene expression changes of hsp47, hsp47-like, col1a1 and col1a2 in muscle that occurred in response to aerobic exercise, the change of type I collagen was most strongly correlated with hsp47 expression. Additionally, col1a1 showed the highest correlation with hsp47-like and col1a2 showed the highest correlation with hsp47. These findings suggest that grass carp Hsp47 and Hsp47-like are closely related to type I collagen synthesis. This study firstly suggests fish aerobic exercise can improve type I collagen content and Hsp47 gene expression in muscle of grass carp.

High stocking density alters growth performance, blood biochemical profiles, and hepatic antioxidative capacity in gibel carp (Carassius gibelio) - Kommaly Onxayvieng; Marina Piria; Mirna Mrkonjić Fuka; Ana Gavrilović; Xiao Liang; Lu Liu; Rong Tang; Li Li; Dapeng Li (Fish Physiology and Biochemistry, 2021)

Prevalence of Depression or Depressive Symptoms in Patients with Narcolepsy: a Systematic Review and Meta-Analysis - Xiao Li; Larry D. Sanford; Qiang Zong; Ye Zhang; Lu Tan; Taomei Li; Rong Ren; Junying Zhou; Fang Han; Xiangdong Tang (Neuropsychology Review, 2021)

Slight Increases in Salinity Improve Muscle Quality of Grass Carp (Ctenopharyngodon idellus) - Xi Zhang; Zhiyuan Shen; Tianpeng Qi; Rujuan Xi; Xiao Liang; Li Li; Rong Tang; Dapeng Li (Fishes, 2021)
Fish muscle quality is an important parameter in the aquaculture industry. In this study, we analyzed and compared the muscle quality of grass carp (Ctenopharyngodon idellus) cultured at salinities of 0‰, 3‰, and 6‰ (GC0, GC3, GC6). There was no significant difference in crude protein and crude fat content of muscle between GC0 and GC3. Crude fat was significantly lower in GC6 compared to the other groups. GC3 and GC6 had higher hydroxyproline content, which suggested that these groups had higher collagen content. GC3 and GC6 had higher contents of free amino acids and umami amino acids than GC0, but there was no significant difference in sweet or sour amino-acid content among groups. GC3 and GC6 had better texture properties, including hardness, gumminess, chewiness, resilience, and springiness, than GC0. GC3 had the highest water-holding capacity among the groups. As the salinity increased, the diameter of muscle fibers decreased and the sarcolemma showed a thickening trend. These results suggest that a slight increase in salinity (i.e., 3‰) can effectively improve the muscle quality of grass carp.

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Associative learning is necessary for airborne pheromones to activate sexual arousal-linked brain areas of female rats - Yao-Hua Zhang; Ming-Ming Tang; Xiao Guo; Xiao-Rong Gao; Jin-Hua Zhang; Jian-Xu Zhang (Behavioral Ecology and Sociobiology, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

Molecular and morphological data reveals new insights into genetic diversity and population structure of Chinese cherry (Prunus pseudocerasus Lindl.) landraces - Tao Chen; Yue-yang Hu; Qing Chen; Yan Wang; Jing Zhang; Hao-ru Tang; Xiao-rong Wang (Genetic Resources and Crop Evolution, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

High immune activation and abnormal expression of cytokines contribute to death of SHIV89.6-infected Chinese rhesus macaques - Ren-Rong Tian; Ming-Xu Zhang; Lin-Tao Zhang; Xiao-Liang Zhang; Hong-Yi Zheng; Lin Zhu; Wei Pang; Gao-Hong Zhang; Yong-Tang Zheng (Archives of Virology, 2015)

Expression and clinical role of TCTP in epithelial ovarian cancer - Chen Chen; Yan Deng; Minhui Hua; Qinghua Xi; Rong Liu; Shuyun Yang; Jian Liu; Jianxin Zhong; Meilan Tang; Shumin Lu; Zhimei Zhang; Xiao Min; et al. (Journal of Molecular Histology, 2015)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Role of Interleukin-22 in liver diseases - Chun-xiao Pan; Jie Tang; Xiao-yu Wang; Fan-rong Wu; Jin-fang Ge; Fei-hu Chen (Inflammation Research, 2014)

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

Genetic diversity and population structure of Chinese Cherry revealed by chloroplast DNA trnQ-rps16 intergenic spacers variation - Tao Chen; Xiao-rong Wang; Hao-ru Tang; Qing Chen; Xiao-jiao Huang; Jiao Chen (Genetic Resources and Crop Evolution, 2013)

Exome Sequencing Identified NRG3 as a Novel Susceptible Gene of Hirschsprung’s Disease in a Chinese Population - Jun Yang; Shengyu Duan; Rong Zhong; Jieyun Yin; Jiarui Pu; Juntao Ke; Xuzai Lu; Li Zou; Hongmei Zhang; Zhidong Zhu; Depeng Wang; Huasheng Xiao; et al. (Molecular Neurobiology, 2013)

Role of Paraoxonase-1 in the Protection of Hydrogen Sulfide-Donating Sildenafil (ACS6) Against Homocysteine-Induced Neurotoxicity - Xiao-Qing Tang; Rong-Qian Chen; Ling Dong; Yan-Kai Ren; Piero Del Soldato; Anna Sparatore; Duan-Fang Liao (Journal of Molecular Neuroscience, 2013)

Formaldehyde Impairs Learning and Memory Involving the Disturbance of Hydrogen Sulfide Generation in the Hippocampus of Rats - Xiao-Qing Tang; Yuan-Yuan Zhuang; Ping Zhang; Heng-Rong Fang; Cheng-Fang Zhou; Hong-Feng Gu; Hui Zhang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2013)

Triterpenoid saponins from the root of Anemone tomentosa - Yi Wang; Wei Kang; Liang-jian Hong; Wen-li Hai; Xiao-yang Wang; Hai-feng Tang; Xiang-rong Tian (Journal of Natural Medicines, 2013)

Tetrandrine citrate eliminates imatinib-resistant chronic myeloid leukemia cells in vitro and in vivo by inhibiting Bcr-Abl/β-catenin axis - Xiao-hua Xu; Yi-chao Gan; Gen-bo Xu; Ting Chen; Hong Zhou; Jin-fen Tang; Ying Gu; Fei Xu; Ying-ying Xie; Xiao-ying Zhao; Rong-zhen Xu (Journal of Zhejiang University-SCIENCE B, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Silicon-mediated amelioration of zinc toxicity in rice (Oryza sativa L.) seedlings - Hai-Hong Gu; Shu-Shun Zhan; Shi-Zhong Wang; Ye-Tao Tang; Rufus L. Chaney; Xiao-Hang Fang; Xin-De Cai; Rong-Liang Qiu (Plant and Soil, 2012)

Overexpression of a cytosolic glyceraldehyde-3-phosphate dehydrogenase gene OsGAPC3 confers salt tolerance in rice - Xiu-Hong Zhang; Xiao-Lan Rao; Hai-Tao Shi; Rong-Jun Li; Ying-Tang Lu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Inhibition of Endogenous Hydrogen Sulfide Generation is Associated with Homocysteine-Induced Neurotoxicity: Role of ERK1/2 Activation - Xiao-Qing Tang; Xin-Tian Shen; Yi-E Huang; Rong-Qian Chen; Yan-Kai Ren; Heng-Rong Fang; Yuan-Yuan Zhuang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Karyotypic, palynological, and RAPD study on 12 taxa from two subsections of section Idaeobatus in Rubus L. and taxonomic treatment of R. ellipticus, R. pinfaensis, and R. ellipticus var. obcordatus - Xiao-Rong Wang; Hao-Ru Tang; Han-Wu Zhang; Bi-Feng Zhong; Wu-Feng Xia; Yuan Liu (Plant Systematics and Evolution, 2009)

Somatic hybrids obtained by asymmetric protoplast fusion between Musa Silk cv. Guoshanxiang (AAB) and Musa acuminata cv. Mas (AA) - Wang Xiao; Xia Huang; Qing Gong; Xue-Mei Dai; Jie-Tang Zhao; Yue-Rong Wei; Xue-Lin Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)

Effects of typical and atypical antipsychotics on glucose–insulin homeostasis and lipid metabolism in first-episode schizophrenia - Ren-Rong Wu; Jing-Ping Zhao; Zhe-Ning Liu; Jin-Guo Zhai; Xiao-Feng Guo; Wen-Bing Guo; Jing-Song Tang (Psychopharmacology, 2006)